Komunikasi Interaksi Simbolik Spoke Person Badja Coffee Dalam Meningkatkan Brand Awareness Lokalate - Amalia Syafira Effendy; Almira Shabrina (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The inevitable evolution of consumer needs drives companies, particularly in the Fast Moving Consumer Goods (FMCG) sector, to continuously seek innovation to enhance competitiveness and have a long-term impact on consumers' lives. Often, these innovations are introduced through events. In this context, the importance of the speaker or spokesperson role as a communicator in building trust and conveying messages to the audience is crucial. This research employs a qualitative case study method, focusing on the